YIELD TEST OF FRESHWATER MICROALGAE POWDER Chlorellasp. ON BASAL MEDIUM - Harifa Syah Putra; Dian Iriani; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Chlorella sp. is a type of green microalgae because it contains chlorophyll a and b and has high nutrition. The growth of these organisms uses various media, one of which is basal medium;meanwhile, there is still little information about the amount of freshwater Chlorella sp. powder produced in the cultivation of the basal medium. The purpose of this study was to determine the yield content of freshwater microalgae Chlorellasp.which was cultivated in basal medium. This research method is experimental and descriptive which consists of three stages, namely sterilization of tools, manufacture of basal media and harvesting of Chlorella sp. Parameters observed consisted of growth and total yield of Chlorella sp.powder. The results showed that the highest number of Chlorellasp. was found on the 12th day of cultivation (2.28 x 106 cells/mL) with the characteristics of the Chlorellasp. powder produced having a smooth texture and dark green color. The yield obtained was 18.36 g (wet weight) and 1.95 g (dry weight). Therefore, the powder of Chlorellasp. can be used for further use as a functional food source.Keywords: Chlorella sp., Basal media, Growth, Yield